Unlocking Behavior Intention of Educator Accountants: Exploring Their Usage of Indonesian Government Program Websites - Probowulan, Diyah; Martiana, Nina (The Indonesian Institute of Science and Technology Research, 2023)
The development of website-based information systems is rapid, so the role of one is needed to meet the need for information and technology facilities. This study aims to find educator accountants' evidence about how users act based on their intentions, such as using websites moderately when learning outside the classroom. Research is being conducted at universities in Indonesia using the UTAUT (Unified Theory of Acceptance and Use of Technology) model to determine behavioural intentions in its use. The data was obtained through a survey with a total of 128 respondents. The results showed that educator accountants' expectations and efforts in using websites for learning still need to be higher because their intentions and behaviour do not have high technology mastery capabilities. The finding implies that the Accounting Department improves educator accountants' competence in mastering technology in government programs. Competency improvement can be made through literacy through training. This research is the first study of the ability to use learning on government program websites with the UTAUT model on educator accountants.